The Cecca Level: A lower Barremian (Lower Cretaceous) lithostratigraphic marker of the Maiolica Formation in the Umbria-Marche Basin (Central Italy) - Christian Conti; Gabriele Gambacorta; Eduardo Di Marcantonio; Marco Chiari; Giovanni Zanchetta; Caterina Morigi; Alessandra Negri (Cretaceous Research, 2027)

Mapping the advancements in floristic knowledge of Italy (2005–2025) - Gianniantonio Domina; Gianluigi Bacchetta; Fabrizio Bartolucci; Marco D’Antraccoli; Lorenzo Peruzzi; Adriano Stinca; Alessandro Alessandrini; Liliana Bernardo; Francesco Boscutti; Daniela Bouvet; Maurizio Bovio; Giacomo Calvia; et al. (Plant Biosystems, 2026)
Based on the evaluation of 3,902 local floristic references published between 2005 and 2025, an update to the floristic knowledge map of Italy is presented. To measure the progress in floristic knowledge across Italy’s administrative regions, the ‘Index of Floristic Knowledge Advancement’ (IFA) is proposed here. This index categorizes regions based on the proportion of potential improvement that has actually been achieved. Results showed an improvement in knowledge, most notably for Northern and Central Italy. Emilia-Romagna emerged as the most comprehensively documented region with the highest IFA value (0.81), followed by Lombardia (0.60), Friuli-Venezia Giulia (0.54), Trentino-Alto Adige and Veneto (0.53). In central Italy, Lazio (0.50), Sardegna (0.45) and Toscana (0.36) registered the highest scores. Over the past twenty years, 453 specific and subspecific taxa have been described from the Italian territory, the majority of which (443) are Italian endemics. Hieracium is the most represented genus (147 taxa). The marked progress documented is likely due to the accelerated impact of coordinated scientific projects, citizen science programs, the development of digital databases, and an increased focus on taxonomic research.

Mitigation of Liquefaction Risk in Layered Soils via Stone Column Drains: Numerical Study and Novel Uncoupled Approach - Gabriele Boccieri; Domenico Gaudio; Pedro Arduino; Riccardo Conti (Computers and Geotechnics, 2026)

The Effect Of Localized Circumferential Residual Stress On Pressurized Stress State Of CT Reconstructed Vessels: A Finite Element Study - Vittorio Lissoni; Martina Schembri; Giulia Luraghi; Alessandro Caimi; Virginia Fregona; Mauro Di Giancamillo; Jessica Bassi; Ferdinando Auricchio; Michele Conti; Gabriele Dubini; Francesco Migliavacca; Jose Felix Rodriguez Matas (Annals of Biomedical Engineering, 2026)
Purpose Residual stresses are intrinsic stresses present in arteries even in the absence of external loads or blood pressure. They originate during growth and remodeling and contribute to vascular mechanical equilibrium. Despite advances in computational methods, incorporating residual stresses into patient-specific vascular models remains challenging. Evidence regarding the influence of circumferential residual stresses on physiological loading in realistic anatomies is still limited. Methods We combined in vitro imaging, mechanical testing, and finite element (FE) simulations to incorporate residual stresses into a pressurized porcine aorta model. Medical images were acquired in both pressurized and zero-stress states, the latter obtained after 2 h of longitudinal cutting. Locally measured mechanical properties from distinct aortic regions were used to define an orthotropic hyperelastic material response. Residual stresses were restored by simulating vessel closure under displacement-controlled boundary conditions with a tied contact interface. Stress distributions were then compared in FE pressurization simulations performed with and without residual stresses. Results Residual stresses substantially influenced the predicted stress fields. They homogenized stress across the vessel thickness and reduced stress concentrations near the lumen. Moreover, lumen cross-sectional areas at 120 mmHg aligned more closely with experimental measurements when residual stresses were included. In contrast, neglecting residual stresses produced an average overestimation of lumen area by 4.84% and stress peaks up to 50% higher in the inner wall. Conclusion This study highlights the importance of accounting for residual stresses in biomechanical vascular simulations. Incorporating them improves prediction accuracy and reduces artificial stress concentrations, which is crucial for patient-specific risk assessment and surgical planning.

Development of a novel NIR spectroscopy-based chemometric model for sourdough bread authentication - Gabriele Lombardi; Federica Violetta Conti; Consuelo Giustizieri; Erica Pontonio; Giuseppe Perri; Cesare Manetti; Carlo Giuseppe Rizzello; Michela Verni (Food Chemistry, 2025)

The invasion history of Ambrosia psilostachya (Asteraceae) in Italy: first record and distribution over more than one century - Chiara Montagnani; Rodolfo Gentili; Gerhard Karrer; Sarah Caronni; Alicia Teresa Rosario Acosta; Michele Adorni; Alessandro Alessandrini; Nicola Maria Giuseppe Ardenghi; Gabriella Buffa; Fabrizio Bartolucci; Alessandra Belisario; Fabrizio Bonali; et al. (Plant Biosystems, 2025)

Chemo-enzymatic flow synthesis of nature-inspired phenolic carbonates and carbamates as antiradical and antimicrobial agents - Sara Vicinanza; Lara Mombelli; Francesca Annunziata; Silvia Donzella; Martina L. Contente; Chiara Borsari; Paola Conti; Gabriele Meroni; Francesco Molinari; Piera Anna Martino; Andrea Pinto; Lucia Tamborini (Sustainable Chemistry and Pharmacy, 2024)

Expression of miRNA from spent pre-implantation embryos culture media - Claudia Omes; Alice Conti; Laura Benedetti; Veronica Tomasoni; Davide De Marchi; Rossella E. Nappi; M. Gabriella Cusella De Angelis; Gabriele Ceccarelli (Reproductive Biology, 2024)

An uncoupled approach for estimating seismic-induced pore water pressures in liquefiable sandy soils - Gabriele Boccieri; Domenico Gaudio; Riccardo Conti (Computers and Geotechnics, 2024)

Geomorphic flood hazard mapping: from floodplain delineation to flood hazard characterization - Andrea Magnini; Michele Lombardi; Armir Bujari; Pietro Mattivi; Iuliia Shustikova; Simone Persiano; Marco Patella; Gabriele Bitelli; Paolo Bellavista; Francesco Lo Conti; Antonio Tirri; Stefano Bagli; et al. (Hydrological Sciences Journal, 2023)

Optical tissue clearing associated with 3D imaging: application in preclinical and clinical studies - Cinzia Brenna; Carolina Simioni; Gabriele Varano; Ilaria Conti; Eva Costanzi; Mattia Melloni; Luca Maria Neri (Histochemistry and Cell Biology, 2022)
Understanding the inner morphology of intact tissues is one of the most competitive challenges in modern biology. Since the beginning of the twentieth century, optical tissue clearing (OTC) has provided solutions for volumetric imaging, allowing the microscopic visualization of thick sections of tissue, organoids, up to whole organs and organisms (for example, mouse or rat). Recently, tissue clearing has also been introduced in clinical settings to achieve a more accurate diagnosis with the support of 3D imaging. This review aims to give an overview of the most recent developments in OTC and 3D imaging and to illustrate their role in the field of medical diagnosis, with a specific focus on clinical applications. Graphical abstract

Physiological host range of Trissolcus mitsukurii, a candidate biological control agent of Halyomorpha halys in Europe - Lucrezia Giovannini; Giuseppino Sabbatini-Peverieri; Leonardo Marianelli; Gabriele Rondoni; Eric Conti; Pio Federico Roversi (Journal of Pest Science, 2022)

First evidence of post‐glacial contraction of Alpine endemics: Insights from Berardia subacaulis in the European Alps - Maria Guerrina; Spyros Theodoridis; Luigi Minuto; Elena Conti; Gabriele Casazza (Journal of Biogeography, 2022)
Aim Late Quaternary glaciations left an enduring imprint on the distribution of species and their genetic structure. The responses of plants endemic to the Alps can be summarized in three major demographic hypotheses: (i) post‐glacial expansion hypothesis; (ii) post‐glacial contraction hypothesis; and (iii) long‐term stability hypothesis. Here we test these hypotheses and reconstruct the time and extent of demographic responses of an endemic plant to the Late Quaternary climate dynamics. Location European Alps. Taxon Berardia subacaulis Vill. (Asteraceae). Methods We used species distribution models to estimate the paleodistribution of B. subacaulis (Asteraceae) throughout the last 28 Ky and generated genome‐wide sequences to estimate current patterns of spatial structure of genetic diversity. We tested five demographic models by integrating the results of the two independent approaches in an Approximate Bayesian Computation framework. Results The species has weak genetic differentiation among populations, with two main genetic groups. Species distribution models showed a reduction in potentially suitable areas for B. subacaulis during the post‐glacial climate warming and demographic models identified a recent split (2.46 Kya) between the two genetic groups and they slightly supported the post glacial contraction hypothesis. Main conclusions Taken together, our results support the post‐glacial contraction of an endemic plant, differing from the main pattern observed for endemics species in the European Alps during the Late Quaternary. The different pattern observed in B. subacaulis might be due to several factors, including the less severe effects of glaciations and the environmental heterogeneity of the South Western Alps, combined with some features of the species (i.e. poor dispersal ability, slow growth and microhabitat preferences). Future research in areas where the ice cover was less extensive will contribute to a more complete understanding of the role of climatic changes in shaping the endemics of the European Alps.

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

Tracking seasonal emergence dynamics of an invasive gall wasp and its associated parasitoids with an open-source, microcontroller-based device - Gabriele Rondoni; Carlo Ricci; Eric Conti (Journal of Pest Science, 2019)

Vicia faba plants respond to oviposition by invasive Halyomorpha halys activating direct defences against offspring - Gabriele Rondoni; Valeria Bertoldi; Robert Malek; Khaled Djelouah; Chiaraluce Moretti; Roberto Buonaurio; Eric Conti (Journal of Pest Science, 2018)

An invasive insect herbivore disrupts plant volatile-mediated tritrophic signalling - Letizia Martorana; Maria Cristina Foti; Gabriele Rondoni; Eric Conti; Stefano Colazza; Ezio Peri (Journal of Pest Science, 2017)

Native egg parasitoids recorded from the invasive Halyomorpha halys successfully exploit volatiles emitted by the plant–herbivore complex - Gabriele Rondoni; Valeria Bertoldi; Robert Malek; Maria Cristina Foti; Ezio Peri; Lara Maistrello; Tim Haye; Eric Conti (Journal of Pest Science, 2017)

Reproductive biology of an Alpic paleo-endemic in a changing climate - Maria Guerrina; Gabriele Casazza; Elena Conti; Carmelo Macrì; Luigi Minuto (Journal of Plant Research, 2016)

Knowing the past to forecast the future: a case study on a relictual, endemic species of the SW Alps, Berardia subacaulis - Maria Guerrina; Elena Conti; Luigi Minuto; Gabriele Casazza (Regional Environmental Change, 2016)

A tale of migrations from east to west: the Irano‐Turanian floristic region as a source of Mediterranean xerophytes - Sara Manafzadeh; Gabriele Salvo; Elena Conti (Journal of Biogeography, 2014)
Aim The Irano‐Turanian ( IT ) floristic region is characterized by high levels of endemicity. Despite its potential role as a cradle of xerophytic taxa for neighbouring areas, its biogeographical history remains poorly studied. H aplophyllum , a diagnostic element of the IT region, was used as a model to discriminate between alternative biogeographical scenarios for the evolution of the region and, more specifically, to investigate whether it served as a source of xerophytes for the colonization of the Mediterranean Basin. Location Irano‐Turanian floristic region (Central Asia and West Asiatic areas) and Mediterranean floristic region (western and eastern parts of the Mediterranean Basin). Methods Three chloroplast DNA regions were sequenced in 77 accessions of Haplophyllum and 37 accessions from other subfamilies of Rutaceae. To elucidate the temporal and spatial evolution of Haplophyllum in the IT and Mediterranean regions, we performed Bayesian molecular dating analyses with four fossil constraints and ancestral range reconstructions, respectively. Results Our molecular dating and ancestral area reconstruction analyses suggest that Haplophyllum originated in the Central Asian part of the IT region during the early Eocene and started to diversify in situ during the early Oligocene, soon after the vanishing of the Tethys Ocean. Our results further imply that Haplophyllum later invaded the eastern Mediterranean Basin in the middle‐to‐late Miocene, concomitantly with the Paratethys Salinity Crisis and rapid palaeobiogeographical changes in the proto‐Mediterranean. Finally, Haplophyllum diversified in the western Mediterranean in the early Pliocene at the end of the Messinian Salinity Crisis. Main conclusions The IT floristic region can serve as a ‘donor’ of xerophytic taxa to ‘recipient’ neighbouring regions, including the Mediterranean floristic region. The climatic/geological processes during the Miocene–Pliocene, by increasing aridity and topographic heterogeneity, facilitated range shifts and allopatric speciation in the region.

Ingestion toxicity of three Lamiaceae essential oils incorporated in protein baits against the olive fruit fly, Bactrocera oleae (Rossi) (Diptera Tephritidae) - Angelo Canale; Giovanni Benelli; Barbara Conti; Gabriele Lenzi; Guido Flamini; Alessandra Francini; Pier Luigi Cioni (Natural Product Research, 2013)

Cytomorphological study on human submandibular gland following treatment with secretagogue drugs - Francesca Testa Riva; Roberto Puxeddu; Francesco Loy; Gabriele Conti; Alessandro Riva (Cell and Tissue Research, 2006)

Fine structure of the spermatozoon of Diopatra neapolitana (Polychaeta, Onuphidae) - Gabriele Conti; Felice Loffredo; Maria Serenella Lantini (Zoomorphology, 2005)